2002
DOI: 10.1046/j.1439-0434.2002.00716.x
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous PCR Detection of the Two Major Bacterial Pathogens of Geranium

Abstract: Xanthomonas campestris pv. pelargonii (Xcp) and Ralstonia solanacearum (Rs) are the two most important bacterial pathogens of commercially cultivated geraniums (Pelargonium spp.), both causing bacterial wilt and leaf spot. Asymptomatic infections are important reservoirs of infections in commercial growing facilities. Our objective was to design a multiplex PCR (Polymerase Chain Reaction) assay to detect infection by either or both of these pathogens. We used a previously characterized PCR primer pair for Xcp … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 9 publications
0
6
0
Order By: Relevance
“…manihotis, a nested PCR (N-PCR) protocol was used to enhance the sensitivity and specificity of detection. In addition, multiplex PCR protocols have been developed in order to detect several pathogens (13) or genetically heterogeneous strains of a single pathovar (24,56) simultaneously.…”
mentioning
confidence: 99%
“…manihotis, a nested PCR (N-PCR) protocol was used to enhance the sensitivity and specificity of detection. In addition, multiplex PCR protocols have been developed in order to detect several pathogens (13) or genetically heterogeneous strains of a single pathovar (24,56) simultaneously.…”
mentioning
confidence: 99%
“…In addition, this study demonstrated the feasibility of multiplexing the GspDm PCR with primers amplifying either a general prokaryotic 16S rDNA target or a general plant mitochondrial ribosomal large subunit target. Multiplex PCR approaches with internal controls have effectively been used in diagnosis of various xanthomonads (Glick et al. , 2002; Berg et al.…”
Section: Discussionmentioning
confidence: 99%
“…The best result for the triple primer pair multiplex-PCR designed in this study was achieved with optimization of primer concentration and annealing temperature which allows detection of either or both of two groups of the pathogen simultaneously. Multiplex-PCR has also been used by Fegan et al (1998) and Glick et al (2002) for concurrent detection of two phytopathogenic bacteria in other studies.…”
Section: Discussionmentioning
confidence: 99%